Respuesta :
Topic : Linear equations in two variables.
Given :
- 3x + 2y = -4 ––– (i)
- x - 2y = 4 ––– (ii)
Solution :
Now,
(i) + (ii)
[tex] \qquad \sf \: { \dashrightarrow 3x + 2y + (x - 2y) = - 4 + 4}[/tex]
[tex] \qquad \sf \: { \dashrightarrow 3x + 2y + x - 2y = 0}[/tex]
[tex] \qquad \sf \: { \dashrightarrow 3x \: \cancel{ + 2y} + x \: \cancel{- 2y} = - 4 + 4}[/tex]
[tex] \qquad \sf \: { \dashrightarrow 4x = 0}[/tex]
[tex] \qquad \bf \: { \dashrightarrow x = 0}[/tex]
Now, substituting the value of x in Eq (i) :
[tex]\qquad \sf \: { \dashrightarrow 3x + 2y = -4}[/tex]
[tex]\qquad \sf \: { \dashrightarrow 3(0) + 2y = -4}[/tex]
[tex]\qquad \sf \: { \dashrightarrow 0 + 2y = -4}[/tex]
[tex]\qquad \sf \: { \dashrightarrow 2y = -4}[/tex]
[tex]\qquad \sf \: { \dashrightarrow y = \dfrac{ - 4}{2} }[/tex]
[tex]\qquad \bf \: { \dashrightarrow y = -2}[/tex]
Therefore, The value of x = 0 and y = -2
The solution to the two given simultaneous equations are; x = 0 and y = -2
How to find the solution to simultaneous equations?
We are given the simultaneous equations;
3x + 2y = -4 -----(eq 1)
x - 2y = 4 ------(eq 2)
Add eq1 and eq2 to get;
4x = 0
x = 0/4
x = 0
Substitute 0 for x in eq 2 to get;
0 - 2y = 4
-2y = 4
y = -4/2
y = -2
Read more about Simultaneous Equations at; https://brainly.com/question/16863577